Legislative challenge to sustainable application of industrialized building system (IBS) - Yunus, Riduan; Yang, Jay (Penerbit UTM Press, 2016)
This paper focuses on the challenges and implications of legislation which has been identified as one of the critical factors in enhancing sustainable deliverables for Industrial Building System (IBS) applications. This study undertakes a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis of Malaysian IBS stakeholders, using survey data collected among the industry players. In terms of legislation, this paper reveals that there is a lack of incentives and regulatory procedures in IBS implementation, a fragmentation of authority and little concern on sustainability issues. Early stage integration, mandatory orders, obligations and government support are the strengths of legislation. The external elements consist of opportunities and threats. For opportunities, five components have been identified, namely legal document integration, certification programmes, long-term benefits, global markets and good image. Threats consist of client-driven decisions, higher initial cost and limited understanding of IBS benefits by the stakeholders.